Evidence in management science related to psychology: benefits, tools, and an example of a community-augmented meta-analysis - Tanja Burgard; Holger Steinmetz (Management Review Quarterly, 2022)
In the field of evidence-based management, the academic-practice gap is well-known and undermines the transfer of scientific findings to evidence-based decision-making. In this paper, we introduce the practical approach of community augmented meta-analysis (CAMA) that serves to ease cumulative evidence formation and dissemination in psychology. CAMA rests on the conviction that a better and faster knowledge transfer requires an increase in the efficiency and quality of evidence integration, timely publication of results, and a broad and easy accessibility. As a potential solution, we describe the platform PsychOpen CAMA that enables the publication of and access to meta-analytic data. We conclude with an empirical example that describes the implementation and presentation of a meta-analysis on gender differences in the intention to start a business using PsychOpen CAMA. Finally, we discuss benefits and potentials of the publication of meta-analytic data on the platform, as well as current methodological and technical limitations.
Keywords: C8; Y8; 650; Meta-analysis; Cumulative evidence; Organizational psychology; Open science; Evidence-based management